1998
DOI: 10.1142/s0129183198000352
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Phosphorus Implantation into Silicon with a Single Parameter Electronic Stopping Power Model

Abstract: We simulate dopant profiles for phosphorus implantation into silicon using a new model for electronic stopping power. In this model, the electronic stopping power is factorized into a globally averaged effective charge Z * 1 , and a local charge density dependent electronic stopping power for a proton. There is only a single adjustable parameter in the model, namely the one electron radius r 0 s which controls Z * 1 . By fine tuning this parameter, we obtain excellent agreement between simulated dopant profile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…For crystalline targets we compare our simulation results directly with secondary ion mass spectroscopy ͑SIMS͒ experimental profiles obtained from the literature. 16,21,32,42 Figures 8-10 show boron implanted into silicon for several energies and implant conditions and they show good agreement with experiments that include very low energy ͑Fig. 8͒, channeling conditions ͑Fig.…”
Section: A Silicon Targetsupporting
confidence: 54%
“…For crystalline targets we compare our simulation results directly with secondary ion mass spectroscopy ͑SIMS͒ experimental profiles obtained from the literature. 16,21,32,42 Figures 8-10 show boron implanted into silicon for several energies and implant conditions and they show good agreement with experiments that include very low energy ͑Fig. 8͒, channeling conditions ͑Fig.…”
Section: A Silicon Targetsupporting
confidence: 54%
“…In this last reference, it was suggested that a ''recovery'' of the deepest damage layers takes place during the hightemperature annealing, in order to explain the difference between experiments and simulations. This hypothesis was tested experimentally by annealing at three different temperatures in the case of the Ag 7 Ϫ experiments, 19 and the experiments indeed confirm that annealing takes place. To correct for the annealing effect, the STM distributions can be fitted to Gaussian functions 19 so that the upper edge of the distribution can be defined.…”
Section: Comparison With Experimental Observations Of Damage Depmentioning
confidence: 88%
“…6͑a͒-͑c͒ we plot the simulation results for typical trajectories of Ag 7 , Ag 15 , and Ag 50 , re-spectively, at an impact energy of 5 keV. The function K z (z) for Ag 7 and Ag 15 has a quadraticlike dependence, whereas for Ag 50 the function seems to be close to linear over the range Ϫ5 -15 Å. Figure 6͑d͒ also shows a near linear behavior of K z (z) over most of the trajectory of an Ag 147 cluster with an impact energy of 15 keV.…”
Section: Pd Scaling For Small Ag N Clusters Versus Large Ag N Clumentioning
confidence: 99%
“…These two ingredients represent the standard features of the REED-MD algorithm; more detailed descriptions can be found in Ref. [3,13,14]. Recently REED-MD has been parallelized with standard MPI (Message Passing Interface) [4], and ions of up to ∼ 100 MeV can be handled with adequate statistics when about 10 4 initial ions are simulated.…”
Section: Implementation Of Reed-mdmentioning
confidence: 99%